Diverse socio-technical aspects of a digital archive of Aboriginal languages - Bow , Catherine (Archives & Manuscripts, 2019)
A socio-technical approach is taken to explore a digital archive of Australian Indigenous cultural heritage. The Living Archive of Aboriginal Languages is considered in terms of what it is currently doing and what it was intended to do. Two ethnographic stories focusing on user interactions and the outcomes of an online survey serve to evaluate the effectiveness of the Archive from the perspective of different users. This is then juxtaposed with a consideration of the original grant application, outlining what was envisaged for the project. This analysis serves to highlight some of the contingent relations and diverse socio-technical aspects of a specific knowledge infrastructure, as it allows multiple forms of interaction, new connections and generative activities as people discover, access and interact with the content now and into the future.